Feeding behavior of ram lambs in the feedlot receiving diets without roughage in different amounts - Santana Junior, Hermogenes Almeida; Barbosa Júnior, Mario Alves; Cardoso-Santana, Elizângela Oliveira; Ferreira, Antônio Hosmylton Carvalho; Silva, Alex Lopes; Abreu Filho, George (Comunicata Scientiae, 2019)
This study aimed to evaluate the feeding behavior of Santa Inês ram lambs in the feedlot receiving diets without roughage in different amounts. Ten castrated Santa Inês male sheep with an average body weight of 20 kg and an average age of four months were used in the experiment. The following treatments were tested: T1 - animals receiving a diet ad libitum (FS100); T2 - animals receiving 95% of the amount of feed supplied in T1 (FS95); T3 - animals receiving 90% of the amount supplied in T1 (FS90); T4 - animals receiving 85% of the amount supplied in T1 (FS85); and T5 - animals receiving 80% of the amount supplied in T1 (FS80). A Latin square (5 × 5) design was adopted, using two simultaneous squares. The times spent feeding, ruminating, performing other activities; the total chewing time; and the number of periods spent feeding and on other activities changed with the reduction in the amount of feed supplied (P<0.05). Number of rumination chews per cud, time per cud, chewing speed, and time per rumination chew did not differ with the reduction of feed supply (P>0.05). Reducing the amount of feed provided to ram lambs consuming diets without roughage changes their feeding behavior.